Hands-on ASP.NET core web API : build API from scratch. (Packt Publishing, 2022)
Learn to build ASP.NET Web APIs with ease with the help of this course. About This Video Get an overview of web APIs in ASP .NET Core and learn about web API request workflow, HTTP status codes, and the different parts of a web API request Understand web API operations such as GET, POST, PUT, and DELETE for collections as well as individual items Build a new RESTful API for a case study through step-by-step instructions In Detail ASP.NET Web API is an ideal platform for building RESTful services and building RESTful applications on .NET Framework. This course explains RESTful Web API request workflow, HTTP status codes, and different parts of a web API request. You will learn to master API Controller concepts that include what are controllers, attributes, and their significance in ASP.NET Web API development. Some of the topics you will learn to include the following: - An overview of web APIs in ASP.NET Core - Web API request workflow - HTTP status codes - Mastering API controller - Building a new RESTful API from scratch - Learn API return types - Understand web API operations This course will provide significant knowledge of implementing API for your next RESTful API-related project. You will be certain to use the building concepts with ease by following a step-by-step approach. You will be confident to instantly apply the ASP.NET Web API tips covered in the course. By the end of the course, you will know how to create a web API project in ASP.NET Core from scratch. Audience This course is for backend web developers who work with APIs by either consuming or exposing APIs and for software architects who want to apply the API concepts to scale and enhance distributed computing in their projects. Basic knowledge of designing a RESTful API, ASP.NET Core, and ASP.NET Core MVC is expected.